Improving the Work Achievement of Employees Through the Leadership Style - Hery Syahrial; Miftahuddin Miftahuddin; Sunaryo Sunaryo (Sekolah Tinggi Manajemen IPMI, 2021)
The purpose of this study was to analyze the factors that influence the work performance of employees in the Percut Sei Tuan sub-district. The sample in this study was 123 employees, using Structure Equation Modeling (SEM) as a data analysis technique. This study concludes that motivation, self-efficacy, and professionalism have a significant effect on leadership style, while competence does not significantly affect leadership style. Leadership style and motivation do not significantly affect work performance, while self-efficacy, professionalism and competence significantly affect work performance. This study provides information that in order to improve employees' work performance, strong leadership is needed and can provide motivation that increases confidence in the ability of employees and also increases professionalism in carrying out duties and responsibilities as a civil servant. Competence is a necessity that must be owned by all employees (civil servants) who are given responsibility by the leadership.